Training and Professional Development in the Police : an Investment in Human Capital or a Bureaucratic Nuisance? - Bohdziewicz, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Actions taken in the area of police officers' trainings are dysfunctional in many respects. Most of the irregularities have been pinpointed by an audit performed in 2005 by NIK (Supreme Audit Office). It is important to note that many of them still persist, which was borne out by research done within an MA seminar conducted in 2011/2012 by the author. The most apparent weak spots include dysfunctions concerning the analysis of training needs or the evaluation of trainings' effectiveness, as well as their low quality compared to contemporary standards.